St. Lucia : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
St. Lucia faces structural challenges that need to be addressed to raise growth durably and reduce poverty. Implementation of planned tax reforms is important to achieve fiscal sustainability. The government's plans to accelerate tourism-related public investment carry significant risks. Competitiveness is a challenge, and structural reforms need to be accelerated to raise the economy's growth potential. Strengthening the supervision of the financial sector is another priority. St. Lucia is one of the most disaster-prone countries in the world. Economic and social statistics need to be improved.